Review of Procedures for Reviewing Indonesian National Work Competency Standards - Bahri, Efri Syamsul; Halmahera, Adityas; Aslam, Mohd Mizan Mohammad (Journal of Multi-Disciplines Science, 2024)
The Indonesian National Work Competency Standards (SKKNI) are mainly used to design and implement job training, conduct training output assessments, and assess a person's current level of skills and expertise. This study aims to review the SKKNI reassessment procedures. This study uses a qualitative method. The research approach, including policy and literature studies, is carried out descriptively. Data comes from regulations, journal articles, and reference books. The results of this study found that the procedure for reviewing the SKKNI was carried out based on the Decree of the Directorate General of Training and Productivity Development of the Ministry of Manpower and Transmigration of the Republic of Indonesia Number Kep.280/Lattas/Xi/2014 Concerning the Guidelines for Procedures for the SKKNI Review. The SKKNI drafting team must make this policy a reference in the SKKNI Review.